Ecophysiology and growth of Eucalyptus in drought condition - dos Santos, Kristiana Fiorentin; Schumacher, Mauro Valdir (Revista Ecologia e Nutrição Florestal - ENFLO, 2016)
The purpose of this literature review is to present some results on the effects of drought on growth, production and ecophysiological behavior of Eucalyptus species. To this will be presented survey data in several countries. Thus, this review will seek to summarize scientific results on the main aspects regarding the efficiency of water use, variables involved in gas exchange and water status of plants (stomatal conductance, transpiration, leaf water potential and photosynthesis) growth characteristics and morphological changes of the genus Eucalyptus sp. Through the literature, it was found, that the treatments with drought affected the use of water, the variables involved in gas exchange and water status of the plants, growth and morphology of Eucalyptus species. Therefore, the search for genetic material tolerant to drought may be relevant to the establishment of forest plantations in areas with water deficit.